2017
DOI: 10.1038/labinvest.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

The evolving concept of cancer stem-like cells in thyroid cancer and other solid tumors

Abstract: The cancer stem-like cell (CSC) hypothesis postulates that a small population of cells in a cancer has self-renewal and clonal tumor initiation properties. These cells are responsible for tumor initiation, growth, recurrence and for resistance to chemotherapy and radiation therapy. CSCs can be characterized using markers such as SSEA-1, SSEA-4, CD44, CD24, ALDEFLUOR and others. CSCs form spheres when they are cultured in serum-free condition in low attachment plates and can generate tumors when injected into i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 110 publications
(207 reference statements)
1
43
0
1
Order By: Relevance
“…24,25 It is well recognized that EMT represents a major mechanism of tumor progression and, in particular, in thyroid carcinogenesis. [26][27][28] Here, through an EMT profiler array, we found that JAM-A was one of the most downregulated genes in ATC and this was confirmed at the protein level. In addition, we showed that JAM-A impaired several hallmarks of thyroid malignant transformation by regulating p53 and GSK3 α/β pathways.…”
Section: In Breast Cancers Both Overexpression and Downregulation Ofmentioning
confidence: 58%
See 3 more Smart Citations
“…24,25 It is well recognized that EMT represents a major mechanism of tumor progression and, in particular, in thyroid carcinogenesis. [26][27][28] Here, through an EMT profiler array, we found that JAM-A was one of the most downregulated genes in ATC and this was confirmed at the protein level. In addition, we showed that JAM-A impaired several hallmarks of thyroid malignant transformation by regulating p53 and GSK3 α/β pathways.…”
Section: In Breast Cancers Both Overexpression and Downregulation Ofmentioning
confidence: 58%
“…EMT is a very complex process during carcinogenesis, in which polarized epithelial cells lose epithelial properties and acquire mesenchymal phenotype, thereby promoting tumor invasion and metastasis . In thyroid tumors, EMT plays an important role in the progression of NTs into PTC and ATC . More important, a strict molecular network of genes involved in cell‐cell adhesion and in tight junction formation, driving EMT, are deregulated in ATC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epithelial-to-mesenchymal transition (EMT) is associated with the development and invasion of thyroid cancers, especially PTC and ATC (Hardy et al 2007, Hardin et al 2017. EMT and autophagy are two distinct events but a cross-talk exists between these two events in a controversial way (Marcucci et al 2017).…”
Section: Autophagy In Initiation and Development Of Thyroid Cancersmentioning
confidence: 99%